Calibration of the electromagnetic calorimeter ECal of the HADES experiment. (October 2020) - Shabanov, A; Borisenko, D; Chudoba, P; Galatyuk, T; Guber, F; Gumberidze, M; Ivashkin, A; Kugler, A; Lalik, R; Morozov, S; Pechenov, V; Petukhov, O; et al.
Abstract: HADES is a large acceptance spectrometer operating at SIS18, GSI, Germany. It is aimed at exploration of QCD phase diagram at the ion beam energies of 1-2 AGeV in the region of high baryonic densities. The new segmented electromagnetic calorimeter (ECal) was built to extend experimental opportunities of the HADES detector. The electromagnetic calorimeter will allow to study new reaction channels involving the production of neutral mesons and neu-tral resonances in elementary and heavy-ion reactions via detection of their two photon decay. An additional advantage of such a device is the resulting improvement of the electron-to-pion separation at large momenta. The detector is based on 978 Cherenkov lead glass modules divided into 6 sectors, and it covers forward angles of 12° < θ < 45° and almost full azimuthal angle. Currently four out of six sectors planned are assembled in the experimental area. The first raw beam data obtained with the ECal detector in Ag+Ag reactions at 1.65 AGeV beam are presented.